Challenges and prospects of virtual libraries in universities in Nigeria (2009)
The challenges and the prospects of virtual library in a university system constitute the focus of this paper. Most university libraries in Nigeria are in deplorable conditions due to inadequate funding. This manifests in libraries having few current books, journals, and other reading resources; staff shortages; deterioration of facilities; inadequate equipment and even library buildings. Such situations are not conducive environment for reading. The virtual library project has the capability of resolving this problem. In this period of information explosion, there is the need for university libraries in Nigeria to use appropriate technology to access the world information in order to enable Universities carry out their traditional functions of teaching, research and public service effectively and efficiently.